Pluteus flammans, a new brightly coloured species in Pluteus sect. Celluloderma (Pluteaceae) from Central Europe - Polhorský, Adam; Justo, Alfredo; Szabóová, Dana; Konyariková, Zuzana; Dima, Bálint; Ševčíková, Hana (Phytotaxa, 2023)
In this article we describe a new species, Pluteus flammans, that is characterised by bright orange-red colours, a villose and translucently striate pileus, and a trichodermal pileipellis. The species is described based on material from Slovakia and Hungary, where it grows on well-decayed angiosperm wood (Quercus spp., Fagus sylvatica, and Tilia sp.). In the phylogenetic analyses (LSU, ITS and TEF1-α) P. flammans appears as sister to the North American Pluteus aurantipes, which also has brightly coloured basidiomes, however this species differs in the bright red stipe, darker colours of the pileus, slightly larger basidiospores, and shorter caulocystidia. Molecular data supports the recognition of both taxa as separate species, and confirms their placement in Pluteus sect. Celluloderma, despite the fact that P. aurantipes was originally considered to belong to Pluteus sect. Hispidoderma.